Charting a path forward in student success. Issue 4 (22nd November 2019) - Deeken, Lynn; Vecchione, Amy; Carr, Allison; Hallman, Shelby; Herzellah, Lara; Lopez, Natalia; Rucker, Rob; Alfieri, Michael; Tenofsky, Deborah; Moore, Anne; Fawley, Nancy; Glover, John; et al.
Abstract : Purpose: This paper aims to demonstrate the variety of ways institutions and their libraries approach student success both conceptionally and operationally. Design/methodology/approach: Librarians from eight different institutions of higher education were given a series of questions about student success on their campuses and in their libraries. They responded with written essays describing their experiences and perspectives. Findings: The contributed pieces in this second installment are collected together and a variety of ways the academic library engage with "student success" are discussed. Initiatives include high-impact practices, fostering academic rapport and creating a sense of belonging, experiential learning and creative spaces and professional development. Originality/value: These examples help to observe what is happening throughout higher education and see potential paths forward at the institutions engaged in this work.